Confucius metaphor of the "attuned ear" - Buljan, Ivana (2008)
ARE THERE ANY METAPHYSICAL/COSMOLOGICAL PRESUPPOSITIONS OF CONFUCIAN TEACHING ABOUT ATTUNEMENT? Although Confucius, as a typical ancient "acosmic" thinker, refused to speak about "the Way of Heaven", or metaphysical/cosmological concepts, nevertheless some of his teachings, especially those concerned about ultimate wisdom, seems to have certain metaphysical/cosmological background. This could be obvious in the case of his metaphor of the "attuned ear" of the sage which enables him to act spontaneously, i.e. when he ought to do is in a complete correspondence with what he wants to do. This highest act of knowing-doing seems to presuppose an insight into a cosmic order of things to which this act is "attuned to". So my presentation will be focused on textual investigation of Confucian and pre-Confucian texts with the aim of finding corroborations that he could inherit some common classical Chinese conceptions about metaphysical/cosmological order of things although he never openly spoke about them. The similar situation could be found in the case of another "acosmic" thinker, namely Buddha, who also refused to speak about metaphysical problems because, in the most cases, they are of no relevance to practical (existential) issues, though all of his (practical) teachings are based on the insight into the "things as they really are".